A Study on the Human Rights Situation in Kirkuk - Shareef, Sanh (The Age of Human Rights Journal, 2023)
Human rights are the principles that seek to protect all human beings around the world from serious political, legal, and social abuses. As a result of the atrocities committed in First and Second World Wars, the United Nations ensures the protection of human rights through several international conventions and instruments, such as the UN Charter and Universal Declaration of Human Rights. Iraq is a signatory to most of the international conventions concerning the protection of human rights. This paper aims to examine the protection of human rights in Kirkuk under the Iraqi Federal Government. The paper’s approach is focused entirely on desk research, with secondary sources being the main sources of information. The study concludes that the Iraqi Federal Government has failed to protect human rights in Kirkuk due to the fragmented security ability of the Federal Government and the dominance of militant groups in the region.